Formação inicial de professores de Língua Portuguesa intermediada pelo Programa Institucional de Bolsa de Iniciação à Docência (PIBID): reflexões a partir do/no/com cotidiano escolar amazônico - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
We weave this research from the idea of an education that is detached from the economic interests of the market and values the differences of the political practices of Portuguese Language teachers in training, negotiated and produced in the networks of/with the school daily lives of the public school system of Manaus-AM, recognizing the uniqueness, creation, invention, resistance and subjectivities of each formative process. We had as a general objective: To problematize the formation of Portuguese Language teachers, former PIBID-UFAM fellows, woven in the networks of knowledge-doings of/with the quotidian. We outlined the following specific objectives a) to problematize the challenges and possibilities of the initial formation of teachers of Portuguese Language in the daily pedagogical practice, according to the experience provided by PIBID; b) to problematize the political practices experienced by the teachers of Portuguese Language in formation, PIBID-UFAM egress fellows, in the daily networks; c) To problematize the knowledge-knowledge woven by the teachers of the Portuguese Language in formation, PIBID-UFAM former PIBID-UFAM fellows, in the pedagogical practices in/with the daily networks of the public schools of Manaus. We were inspired by the studies of those who work with the daily life of schools in Brazil, such as Nilda Alves, Inês Barbosa de Oliveira; Carlos Eduardo Ferraço, among others, in the light of the theory of daily life, by the French historian and philosopher Michel de Certeau. We dive into the narratives of the experiences/formative experiences of undergraduates of Portuguese Language, fellows of PIBID-UFAM (2018-2019), to problematize the political practices of training and self-training woven outside the school, the university and PIBID, which are often dismissed by the research of modern scientificity. In this way, we seek to rescue singular and collective experiences, remembered, shared and re-signified by us and by the author-narrators of this study. For this, we respect and value the specificities, tactics, creativity, and subjectivities of all the thinking-practitioners involved in this study. Thus, we understand the imperiousness of a teacher education woven in everyday networks, in order to value the experiences and resistances of emancipatory political practices led in a singular and heterogeneous way by each thinking-practitioner, taking into consideration the tensioning of a hegemonic education in favor of an emancipatory, multicultural, ethical, plural and inclusive education.
Keywords: Professores - Formação; Língua portuguesa - Aspectos sociais; Língua portuguesa - Estudo e ensino (Educação permanente); CIENCIAS HUMANAS: EDUCACAO; Professores de Língua Portuguesa em formação; Redes cotidianas; Cotidianos escolares; PIBID